A conflict of visions: Ideas shaping wildlife trade policy toward African megafauna - ʼt Sas‐Rolfes, M; Gooden, J (Wiley Open Access, 2024)
Among factors that threaten wild populations of African megafauna, wildlife trade has gained prominence as a global policy issue, with concerted international campaigns aiming to influence the trade of species such as elephants, rhinos and lions. Trade policy is strongly contested, confounding attempts to develop coherent approaches across jurisdictions and through international mechanisms such as the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). This undermines conservation efforts. Understanding the drivers of such conflict may help to address this problem. Scholars of political science increasingly recognise the power of ideas as drivers within policy processes. Guided by this literature, we developed an analytical framework and conducted a thematic analysis to examine the ideas driving wildlife trade policy conflict. Our nested case study approach examined debates over trade policy toward African elephants, rhinos and lions at two levels: the international policy arena of CITES and within a single country, South Africa. Informed by earlier literature, we tracked the evolution of international trade policy debates over a 4‐year period (2016–2019) and analysed submissions to a national policy review process in South Africa that took place during 2020. During the study period, state and non‐state actors contributed to vigorous trade policy debates within seven key thematic issues across the case study species. Arguments were driven by both cognitive ideas, which specify cause‐and‐effect relationships, and normative ideas, which are values‐based and especially salient elements of anti‐trade stances. Fusing these cognitive and normative ideational elements, we identified three distinct overarching narratives relating to wildlife trade policy. These three narratives align with broader environmental policy and political narratives and elucidate inherent tensions within the CITES arena. They also reveal differing ethical interpretations and perceptions of risk and precaution. Policy implications. Wildlife trade policy conflict is driven at least in part by competing ideological visions, which may be entrenched by the CITES Appendix listing system. The structural role of CITES in perpetuating this polarisation—and the consequences thereof—warrants further research. Read the free Plain Language Summary for this article on the Journal blog.